Financial Performance Review of ESSO Malaysia BERHAD in Comparison to the Other EXXONMobil's Downstream Subsidiary ESSO Thailand - Pratama, Arief Rahman; Noveria, Ana (Journal of Business and Management, 2014)
In this research, Researcher analyze about the past financial condition of Esso Malaysia Berhad, as the latest issue of ExxonMobil downstream divestiture, in comparison with another ExxonMobil downstream in Asia, which is Esso Thailand. Researcher interest in assess the financial performance of Esso Malaysia Berhad before Esso Malaysia Berhad Divested in August 2011. Researcher wants to analyze the performance in according to the divestiture issues. ExxonMobil stated that Esso Malaysia Berhad had a continuous decline financial performance, and as the ExxonMobil downstream subsidiary, Esso Malaysia Berhad Contribute less than the other ExxonMobil Downstream industries. In assessing the financial performance of Esso Malaysia Berhad, researcher will use several methods which are time-series analysis (Compound Annual Growth Rate), cross-sectional analysis, common-size financial statement analysis, and DuPont system of Analysis. In overall, unfortunately Esso Malaysia Berhad has better performance than Esso Thailand in terms of financial ratios analysis, Compound Annual Growth Rate Comparison, cross-sectional analysis and DuPont system of analysis. Whereas, both Esso Malaysia Berhad and Esso Thailand have a similar performance in terms of common-size financial statement.Keywords: financial performance review, CAGR, financial ratios, divestiture, Oil and Gas industry, Downstream Industry